Nonthermal Plasma Treatment for Electrocatalysts Structural and Surface Engineering - Tang, Jiayi; Su, C.; Shao, Zongping (WILEY-V C H VERLAG GMBH, 2022)
Structure and surface modification of electrocatalysts demonstrates a promising lead for achieving excellent electrocatalytic activity and efficiency. Among various surface modification strategies, nonthermal plasma technique possesses an irreplaceable role due to the merits of simple but controllable operation procedure, low pollution, low cost, and easy scale-up for practical applications. Nonthermal plasma treatment, as a powerful tool for material surface and structural engineering, can mainly benefit the electrocatalytic reactions in the following aspects: surface atom doping or reconstructing, introducing vacancies or defects, surface partially reducing or oxidizing, and increasing the porosity or roughness. Given to its flexibility, plasma modification is gaining a noticeable popularity, and great progress has been made in applying plasma for optimizing surface properties of the mainstream electrocatalysts, including metal-free carbon materials, metal oxides, and other compounds, as well as organometallic electrocatalysts, etc. This review first summarizes the recent advances in nonthermal plasma modification for achieving desirable electrocatalytic behaviors, aiming to highlight the cutting-edge function designs of electrocatalysts with plasma technology. It is hoped that this work can give some inspiration for the development of highly efficient electrocatalysts.